Age and etiology of childhood epidermolysis bullosa mortality. (April 2015) - Hon, Kam Lun Ellis; Li, Joshua J.; Cheng, Bernadette L.; Luk, David C.; Murrell, Dedee F.; Choi, Paul C. L.; Leung, Alexander K. C.
Abstract Epidermolysis bullosa (EB) is a heterogeneous group of congenital blistering diseases that are usually present in the neonatal period. They are characterized by blister formation in response to rubbing or frictional trauma. EB is classified into three major categories, each with many subtypes based on the precise location at which separation or blistering occurs, namely epidermolysis bullosa simplex (EBS), junctional epidermolysis bullosa (JEB), and dystrophic epidermolysis bullosa (DEB). We describe the causes and ages of death of three cases of EB in Hong Kong. A 24-year-old male with EBD diagnosed in the neonatal period lived a withdrawn life after completing secondary school and died of metastaic squamous cell carcinoma. Two neonates of consanguineous Pakistani parents, one with JEB and the other with EB-Pyloric Atresia variant, died of sepsis in infancy. We performed an extensive literature review of the causes and ages of death of these diseases. EB is a heterogeneous inherited blistering skin disease associated with significant morbidity and mortality. EBS is occasionally associated with death at early ages with sepsis. Patients with JEB usually died of sepsis at young age. DEB patients often survive to adulthood and die of cardiopulmonary and renal complications. Squamous cell carcinoma and metastases are unique in DEB.